2020
DOI: 10.29252/aassjournal.893
|View full text |Cite
|
Sign up to set email alerts
|

Standing Handball Throwing Velocity Estimation with a Single Wrist-Mounted Inertial Sensor

Abstract: Background. It is well known that overarm throwing is one of the most performed activities in the handball. Shoulder and glenohumeral injuries incidence are high in handball because of both pass, and shooting activity was executed repeatedly in high angular speed. Objectives. This study set out to investigate the usefulness of inexpensive commercial inertial movement sensors for prediction of throwing velocity in handball. Methods. After the IMU sensor (500 Hz) placed to the wrist of the dominant arm, players … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In their study [7], Gençoğlu et al had people shoot balls at oneminute rest intervals. They used the Generalized Linear Model, Gradient Augmented Trees, and Support Vector Machine to predict the ball flight.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study [7], Gençoğlu et al had people shoot balls at oneminute rest intervals. They used the Generalized Linear Model, Gradient Augmented Trees, and Support Vector Machine to predict the ball flight.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, the Δt value is 0.05 s. When the GWN model (discrete white noise model) in Equation ( 5) is added, Equation ( 6) is obtained. The output response of the system is then given by equation (7).…”
Section: 𝑉 𝑥 (𝑘 + 1) = 𝑉 𝑥 (𝑘)mentioning
confidence: 99%
“…On the other hand, IMUs do not need a fixed location on the field for measuring ball velocity, thus they can be used on many different occasions. The previous studies demonstrated the potential use of IMUs for estimation of the ball velocity in different overhead-throwing sports, including baseball [11][12][13].…”
Section: Introductionmentioning
confidence: 99%